Effect of Using Cassava Pulp on Bio-fertilizer Pellet to Nutrient Elements Value - CHANTHIP, Phonepadith; Phouthaxay, Phonesavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study was aimed to utilize waste from cassava factories such as cassava pulp in the production of bio-fertilizers pellets, as well as to investigate the nutritional elements value from the production of fertilizer with a mixture of cassava pulp that varies from 0-30% of each fertilizer formula containing: manure, waste vegetables, bio-fertilizer and Extract micro-organism (EM). Using the Completely Randomized Design (CRD) experimental model that consists of 3 replications and 6 treatments. In the production of this fertilizer was fermented in a black tank and will take a total of 45 days of fermentation. Then bring the fertilizer to be compressed into pellets and the pellets will be taken to analysis the nutrient elements value, such as pH, OM, N, P2O5 and K2O before and after being compressed into pellets. From the research on the nutrient value, it was shown that: in each fertilizer formula, there were significance at 95%. And the nutrient elements value was higher in cassava pulp 15% (T3) of fertilizer content both before and after by OM (34.13%), N (0.62%), P2O5 (55.55 mg/kg), K2O (79.00 mg/kg) and pH = 7.08 value. When compared with the treatments group was significance at p<0.05. and followed by the treatment with cassava pulp 10% of fertilizer content (T2). Moreover, when compared with the control (T1 = 100% bio-fertilizer) with nutrients elements value both before and after such as pH, OM, N, P2O5 and K2O was showed significantly difference and the nutrients elements value was increased up to 3-5 times. From this study, it can be said that cassava pulp can help increase the nutrients elements value in each fertilizer formula and there is a statistical relationship.